Luminescent phosphate fluorescent glass ceramic for gamma-ray radiation dose detection as well as preparation method and application of luminescent phosphate fluorescent glass ceramic
By doping Gd3+ ions in NaCaPO4 glass ceramics, glass ceramic materials rich in nanocrystals were prepared, which solved the problems of low sensitivity and difficult preparation of existing gamma radiation dose detection materials, and achieved efficient and stable gamma radiation detection.
Patent Information
- Application Number
- CN202311259571.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
The existing gamma ray radiation dose detection materials have low OSL sensitivity, difficulty in preparation, and have problems with material fading and tidal solubility, which limits their application.
Gd3+ ion-doped NaCaPO4 glass ceramic material is prepared by melt quenching to form glass ceramic rich in NaCaPO4 nanocrystals, with good thermal stability and radiation detection performance.
A wide range of gamma radiation dose detection and high linearity CW-OSL dose response are achieved, and the material has good thermal stability and luminous stability, which is suitable for the field of radiation dose monitoring.
Smart Images

Figure CN119707292A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of phosphate fluorescent glass ceramics, and in particular to a luminescent phosphate fluorescent glass ceramic for gamma-ray radiation dose detection, a preparation method thereof, and applications thereof. Background Art
[0002] Currently, OSL (OSL) phosphors such as Al₂O₃:C and BeO have been practically applied as phosphors for personal dosimetry. However, their low OSL sensitivity and difficulty in preparation have stimulated the research and development of new dosimetry materials. Furthermore, alkali-halide phosphors such as Eu-doped BaFBr (BaFBr:Eu) and Eu-doped CsBr (CsBr:Eu) have been put into practical use as dosimetry materials for medical and dental diagnostics, as well as for computed radiography. However, despite their high OSL sensitivity, these phosphors are limited in their application due to inherent fading and tidal solubility issues. Furthermore, Dy-Eu co-doped phosphors, due to the energy transfer between Dy and Eu, present uncontrollable and complex energy transfer, making them unsuitable for radiation dosimetry applications. Against this backdrop, researchers are continuing to develop new OSL dosimetry materials, such as single crystals, polycrystalline powders, glasses, and glass-ceramics, not only for personal dosimetry and medical imaging, but also for environmental, space, and emergency dosimetry. Among them, borophosphite glass with a formula of Na2O-CaO-P2O5-B2O3-ZrO2 exhibits excellent optical properties, low dispersion, low phonon energy, and excellent transparency from the ultraviolet to the near-infrared region, making it an ideal matrix material for rare earth ion doping. Currently, research on OSL radiation dosing materials for NaCaPO4 glass-ceramics is limited. Therefore, further research is urgently needed on the OSL properties of NaCaPO4 glass-ceramics doped with other rare earth ions as a matrix material. Summary of the Invention
[0003] The technical problem to be solved by the present invention is to provide a luminescent phosphate fluorescent glass ceramic for gamma-ray radiation dose detection and a preparation method thereof in response to the deficiencies of the existing technology. The glass ceramic material has good thermal stability, realizes wide gamma-ray radiation dose detection and high CW-OSL dose response linearity, and the preparation method of the glass ceramic material is simple and efficient.
[0004] The technical solution adopted by the present invention to solve the above technical problems is: a luminescent phosphate fluorescent glass ceramic material for gamma ray radiation dose detection, the luminescent phosphate fluorescent glass ceramic material is composed of: P2O5 4-7%, CaO 21-24%, Na2O 23-26%, B2O3 42-45%, ZrO2 1-4%, the glass matrix is doped with Gd3+ , doped in the form of a compound, wherein the doped gadolinium-containing compound accounts for x of the total mass of other raw materials, 0.1≤x≤0.75.
[0005] Gd2O3 can be obtained by mixing, grinding, calcining, melting and quenching, grinding, pressing and molding, and cooling to the glass softening point of raw materials Na2CO3, CaCO3, NH4H2PO4, B2O3 and Gd2O3. 3+ Ion-doped NaCaPO4:xGd 3+ Glass ceramics, wherein the glass matrix is doped with Gd 3+ The doped gadolinium compound Gd2O3 accounts for 0.1-0.75% of the total mass of other raw materials. NaCaPO4 nanocrystals are precipitated in the glass matrix. The glass ceramic material has high crystallinity and transparency. Its excitation spectrum is in the ultraviolet region. After adjustment, the appropriate Gd 3+ The doping amount can achieve a good linear dose response to gamma rays in the range of 0.01-1000Gy. The sample of the present invention has good thermal stability and wide radiation dose response performance, and can be used as a new type of fluorescent material in the field of radiation dose monitoring.
[0006] The glass-ceramic material of the present invention adopts a precursor glass (wt%) Na2O-CaO-P2O5-ZrO2 glass matrix, wherein P2O5 and B2O3 provide a rigid structure, so that the glass-ceramic material has the advantages of high hardness and good mechanical properties, and at the same time creates nucleation and boundary conditions for the glass crystallization process; the role of introducing Na2O and CaO is to provide the necessary component elements for the precipitation of nanocrystalline NaCaPO4, and the role of ZrO2 is to lower the melting point of the mixture, making heating more convenient.
[0007] The matrix glass of the glass-ceramic material of the present invention has good forming ability and thermal stability, low phonon energy and good transparency, and is a good matrix for rare earth ions. It has a low forming temperature and low raw material cost. The CW-OSL dose response m value in the range of 0.1-1000Gy is fitted to 0.928, close to 1, and the linear fitting R value in the range of 50-1000Gy is 2 =0.9992, the OSL output signal intensity of the sample has almost no change after repeated testing, and the doped Gd 3+ By doping into nanocrystalline NaCaPO4 without destroying the structure of the crystal, a large number of rare earth luminescent ions are embedded in a low phonon energy environment, which is beneficial to reducing the probability of non-radiative transitions and improving the luminescence efficiency.
[0008] The present invention provides a method for preparing luminescent phosphate fluorescent glass ceramics, comprising the following steps:
[0009] 1) Raw material preparation: weigh the raw materials and mix them evenly to obtain a mixture powder;
[0010] 2) Melting and quenching: The powder obtained in step 1) is calcined, melted, and then quenched to obtain a precursor glass, which is then ground to obtain a glass powder;
[0011] 3) Tableting: Pour the glass powder obtained in step 2) into a mold and press it into a green disc;
[0012] 4) Heat treatment: The green disc obtained in step 3) is heat treated and cooled to room temperature to obtain rare earth Gd 3+ Doped NaCaPO4 fluorescent glass ceramics.
[0013] Preferably, in step 2), the calcination temperature is 1250-1350° C., and the calcination time is 1-4 hours;
[0014] The melt was poured into deionized water for quenching.
[0015] Preferably, in step 3), a hydraulic press is used for pressing, and the hydraulic press uses a pressure of 20-50 MPa and a holding time of 60-90 seconds.
[0016] Preferably, in step 4), the heat treatment temperature is 400° C.-550° C., and the heat treatment time is 3-6 hours.
[0017] As a preference, in step 4) rare earth Gd is obtained 3+ The CW-OSL dose response of the NaCaPO4-doped fluorescent glass-ceramic material is fitted to a value of 0.928 in the range of 0.1-1000 Gy, which is close to 1. The linear fitting R 2 =0.9992.
[0018] Specifically, the present invention provides a rare earth Gd 3+ The preparation method of ion-doped NaCaPO4 glass-ceramic material is carried out according to the following steps:
[0019] 1) Raw material preparation: Using Na2CO3, CaCO3, NH4H2PO4, B2O3, and Gd2O3 as raw materials, according to the mass percentages of P2O 54-7%, CaO 21-24%, Na2O 23-26%, B2O3 42-45%, and ZrO2 1-4%, where the gadolinium-containing compound accounts for x% of the total mass of the other raw materials, 0.1≤x≤0.75, the raw materials are weighed and ground in an agate mortar for 2-4 hours. The mixture is thoroughly mixed to obtain a powder mixture;
[0020] 2) Melting and Quenching: The powder obtained in step 1) is placed in a muffle furnace at a temperature of 1250-1350° C. and calcined for 1-4 hours. The melt in the high-purity corundum crucible is quickly poured onto a steel plate and quenched to obtain a precursor glass. The precursor glass is then ground for 2-4 hours to obtain a glass powder.
[0021] 3) Tableting: Weigh about 0.15-0.2 g of the powder obtained in step 2) into a mold with a diameter of 10-20 mm and press into green discs using a hydraulic press at a pressure of 20-50 MPa for 60-90 seconds;
[0022] 4) Heat treatment: The green disc obtained in step 3) is placed in a muffle furnace for heat treatment at a temperature of 400°C-550°C for 3-6 hours, and then cooled naturally to room temperature to obtain rare earth Gd 3+ Doped NaCaPO4 fluorescent glass ceramic materials.
[0023] The present invention provides an application of luminescent phosphate fluorescent glass ceramics in gamma-ray radiation dose detection.
[0024] Compared with the prior art, the advantages of the present invention are:
[0025] 1. The present invention first obtains the precursor glass by melt quenching method, and then partially crystallizes it by heat treatment to obtain a glass ceramic material rich in a large number of NaCaPO4 nanocrystals. The borophosphate matrix glass has good forming ability and thermal stability, as well as low phonon energy and good transparency. It is a good matrix for rare earth ions, has low molding temperature, low raw material cost, and a large amount of rare earth luminescent ions Gd 3+ It can be embedded in a low phonon energy environment, which is beneficial to improving its luminous intensity, reducing the probability of non-radiative transitions, and improving luminous efficiency.
[0026] 2. The fluorescent glass ceramics of the present invention are prepared by using rare earth element Gd 3+ The doping of Gd single doped single ion has a certain energy level transition and energy transfer, strong controllability in gamma ray irradiation, simple energy transfer, high stability and a wide radiation measurement range. The CW-OSL dose response is achieved in the range of 0.1-1000Gy. The value of m is fitted to 0.928, close to 1, and the linear fitting R is in the range of 50-1000Gy. 2 =0.9992, the OSL output signal intensity of the sample hardly changes after repeated testing, and it has good thermal stability and luminescence stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] FIG1(a) is an XRD spectrum of the fluorescent glass in Examples 1, 2, 3, and 4 of the present invention.
[0028] FIG1( b ) is a schematic diagram of a model of NaCaPO4 crystals precipitated from glass ceramics in Examples 1, 2, 3, and 4 of the present invention;
[0029] FIG2(a) is a TEM spectrum of the fluorescent glass ceramic in Example 1 of the present invention (NaCaPO4 crystals can be seen in the figure),
[0030] FIG2( b ) is a TEM spectrum of the fluorescent glass-ceramic in Example 1 of the present invention (lattice fringes of precipitated NaCaPO 4 crystals can be seen in the figure);
[0031] FIG3-1(a) is an EDS element mapping image of all elements of the fluorescent glass ceramic in Example 3 of the present invention.
[0032] FIG3-1( b ) is a SEM scanning image of the fluorescent glass ceramic in Example 3 of the present invention.
[0033] FIG3-2(a) is an EDS element mapping image of the Na element in the fluorescent glass ceramic in Example 3 of the present invention.
[0034] FIG3-2( b ) is an EDS element mapping image of the Ca element in the fluorescent glass ceramic in Example 3 of the present invention.
[0035] FIG3-2(c) is an EDS element mapping image of the P element of the fluorescent glass ceramic in Example 3 of the present invention.
[0036] FIG3-2(d) is an EDS element mapping image of the O element of the fluorescent glass ceramic in Example 3 of the present invention.
[0037] FIG3-2(e) is an EDS element mapping image of the Al element in the fluorescent glass ceramic in Example 3 of the present invention.
[0038] FIG3-2( f ) is an EDS element mapping image of the Gd element in the fluorescent glass-ceramic in Example 3 of the present invention;
[0039] FIG4( a ) is a 3D spectrum diagram of the excitation emission of the fluorescent glass ceramic in Example 3 of the present invention.
[0040] FIG4( b ) is an excitation spectrum diagram of the fluorescent glass ceramics in Examples 1, 2, 3, and 4 of the present invention.
[0041] FIG4( c ) is an emission spectrum of the fluorescent glass-ceramics in Examples 1, 2, 3, and 4 of the present invention;
[0042] Figure 5 is the Fourier infrared spectrum of the fluorescent glass-ceramic in the embodiment of the present invention;
[0043] Figure 6The OSL attenuation curves and OSL integrated intensity changes of the fluorescent glass ceramics in Examples 1, 2, 3, and 4 of the present invention are shown;
[0044] Figure 7 : CW-OSL attenuation curve and exponential fitting curve of the fluorescent glass ceramics in Examples 1, 2, 3, and 4 of the present invention;
[0045] Figure 8 TL curve of the fluorescent glass ceramic in Example 3 of the present invention;
[0046] FIG9( a ) is a CW-OSL dose response curve (0.01-1000 Gy) of the fluorescent glass-ceramic in Example 3 of the present invention;
[0047] FIG9( b ) is a CW-OSL attenuation curve (50-1000 Gy) of the fluorescent glass-ceramic in Example 3 of the present invention;
[0048] Figure 10 This is the OSL cycle characteristic curve of the fluorescent glass ceramic in Example 3 of the present invention. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is described in detail below with reference to the accompanying drawings and embodiments.
[0050] Example 1:
[0051] (1) Weigh Na2CO3, CaCO3, NH4H2PO4, B2O3 and Gd2O3 according to the raw material ratio, and weigh the raw materials according to the mass percentage: P2O5 4%, CaO 23%, Na2O 24%, B2O3 45%, ZrO2 4%, Gd2O3 0.1%, place the raw materials in an agate mortar and grind them for 4 hours to obtain a uniformly mixed powder, and transfer it to a high-purity corundum crucible;
[0052] (2) placing the powder obtained in step (1) in a muffle furnace at a temperature of 1250° C. and calcining for 4 hours, quickly pouring the melt in the high-purity corundum crucible into deionized water for quenching to obtain a precursor glass, and then transferring it to an oven for drying to obtain a solid glass;
[0053] (3) grinding the solid glass obtained in step (2) in an agate mortar for 2 hours to obtain glass powder;
[0054] (4) Weigh 0.15 g of the powder obtained in step (3) and pour it into a mold with a diameter of 20 mm. Press it into a green disc using a hydraulic press with a holding pressure of 20 MPa for 90 seconds.
[0055] (5) The green disc obtained in step (4) is placed in a muffle furnace for heat treatment at a temperature of 420°C for 3 hours and then cooled to room temperature to obtain rare earth Gd 3+ Doped NaCaPO4 fluorescent glass ceramic materials.
[0056] The XRD pattern of the NaCaPO4 glass ceramic obtained in step (5) is shown in Figure 1. Both the crystal peak and the amorphous peak exist, and the peak position and intensity of the crystal peak correspond to the PDF card of NaCaPO4, indicating the existence of the corresponding crystalline phase. Under the excitation of 275nm light source, the emission spectrum measured is shown in Figure 4(b), showing that Gd 3+ Characteristic emission peaks of NaCaPO4-doped phosphate glass ceramics. The XRD spectrum of the fluorescent glass is shown in Figure 1(a), the model of the precipitated NaCaPO4 crystal is shown in Figure 1(b), the TEM spectrum of the fluorescent glass ceramic (the precipitated NaCaPO4 crystals can be seen in the figure) is shown in Figure 2(a), the TEM spectrum of the fluorescent glass ceramic (the lattice fringes of the precipitated NaCaPO4 crystals can be seen in the figure) is shown in Figure 2(b), the excitation spectrum of the fluorescent glass ceramic is shown in Figure 4(b), the emission spectrum of the fluorescent glass ceramic is shown in Figure 4(c), and the Fourier transform infrared spectrum of the fluorescent glass ceramic is shown in Figure 4(d). Figure 5 As shown in Figure 2, the OSL decay curve and OSL integral intensity changes of fluorescent glass ceramics are shown in Figure 2. Figure 6 As shown in Figure 2, the CW-OSL decay curve and exponential fitting curve of the fluorescent glass ceramics are shown in Figure 2. Figure 7 shown.
[0057] Example 2:
[0058] (1) Weigh the raw materials Na2CO3, CaCO3, NH4H2PO4, B2O3 and Gd2O3 according to the raw material ratio, and weigh the raw materials according to the mass percentage: P2O5 5%, CaO 22%, Na2O 26%, B2O3 44%, ZrO2 3%, Gd2O3 0.25%. Place the raw materials in an agate mortar and grind them for 3 hours to obtain a uniformly mixed powder, and transfer it to a high-purity corundum crucible;
[0059] (2) placing the powder obtained in step (1) in a muffle furnace at a temperature of 1300° C. and calcining for 3 hours, quickly pouring the melt in the high-purity corundum crucible into deionized water for quenching to obtain a precursor glass, and then transferring it to an oven for drying to obtain a solid glass;
[0060] (3) grinding the solid glass obtained in step (2) in an agate mortar for 3 hours to obtain glass powder;
[0061] (4) Weigh 0.2 g of the powder obtained in step (3) and pour it into a mold with a diameter of 20 mm. Press it into a green disc using a hydraulic press with a holding pressure of 30 MPa for 80 seconds.
[0062] (5) The green disc obtained in step (4) is placed in a muffle furnace for heat treatment. The heat treatment temperature is first kept at 520°C for 3 hours and then naturally cooled to room temperature to obtain rare earth Gd 3+ Doped NaCaPO4 fluorescent glass ceramic materials.
[0063] The XRD pattern of the NaCaPO4 glass ceramic obtained in step (5) is shown in Figure 1. Both the crystal peak and the amorphous peak exist, and the peak position and intensity of the crystal peak correspond to the PDF card of NaCaPO4, indicating the existence of the corresponding crystalline phase. Under the excitation of 275nm light source, the emission spectrum measured is shown in Figure 4(b), showing that Gd 3+ The characteristic emission peak position of the doped NaCaPO4 phosphate glass ceramics. The XRD spectrum of the fluorescent glass is shown in Figure 1 (a), the model of the precipitated NaCaPO4 crystal is shown in Figure 1 (b), the excitation spectrum of the fluorescent glass ceramics is shown in Figure 4 (b), the emission spectrum of the fluorescent glass ceramics is shown in Figure 4 (c), and the Fourier transform infrared spectrum of the fluorescent glass ceramics is shown in Figure 4 (d). Figure 5 As shown in Figure 2, the OSL decay curve and OSL integral intensity changes of fluorescent glass ceramics are shown in Figure 2. Figure 6 As shown in Figure 2, the CW-OSL decay curve and exponential fitting curve of the fluorescent glass ceramics are shown in Figure 2. Figure 7 shown.
[0064] Example 3:
[0065] (1) Weigh the raw materials Na2CO3, CaCO3, NH4H2PO4, B2O3 and Gd2O3 according to the raw material ratio, and weigh the raw materials according to the mass percentage: P2O5 6%, CaO 23%, Na2O 25%, B2O3 44%, ZrO2 2%, Gd2O3 0.5%, place the raw materials in an agate mortar and grind them for 2 hours to obtain a uniformly mixed powder, and transfer it to a high-purity corundum crucible;
[0066] (2) placing the powder obtained in step (1) in a muffle furnace at a temperature of 1250° C. and calcining for 2 hours, quickly pouring the melt in the high-purity corundum crucible into deionized water for quenching to obtain a precursor glass, and then transferring it to an oven for drying to obtain a solid glass;
[0067] (3) grinding the solid glass obtained in step (2) in an agate mortar for 2 hours to obtain glass powder;
[0068] (4) Weigh 0.15 g of the powder obtained in step (3) and pour it into a mold with a diameter of 10 mm. Press it into a green disc using a hydraulic press with a holding pressure of 20 MPa for 60 seconds.
[0069] (5) The green disc obtained in step (4) is placed in a muffle furnace for heat treatment. The heat treatment temperature is first kept at 420°C for 2 hours, then kept at 520°C for 2 hours, and finally cooled naturally to room temperature to obtain rare earth Gd 3+ Doped NaCaPO4 fluorescent glass ceramic materials.
[0070] The XRD pattern of the NaCaPO4 glass ceramic obtained in step (5) is shown in Figure 1. Both the crystal peak and the amorphous peak exist, and the peak position and intensity of the crystal peak correspond to the PDF card of NaCaPO4, indicating the existence of the corresponding crystalline phase. Under the excitation of 275nm light source, the emission spectrum measured is shown in Figure 4(b), showing that Gd 3+ Characteristic emission peak position of doped NaCaPO4 phosphate glass ceramics. The XRD spectrum of the fluorescent glass is shown in Figure 1(a), the model of the precipitated NaCaPO4 crystal is shown in Figure 1(b), the EDS element mapping image of all elements of the fluorescent glass ceramic is shown in Figure 3-1(a), the SEM scanning image of the fluorescent glass ceramic is shown in Figure 3-1(b), the EDS element mapping image of the Na element of the fluorescent glass ceramic is shown in Figure 3-2(a), the EDS element mapping image of the Ca element of the fluorescent glass ceramic is shown in Figure 3-2(b), and the EDS element mapping image of the P element of the fluorescent glass ceramic is shown in Figure 3-2(c), the EDS element mapping image of the O element of the fluorescent glass ceramic is shown in Figure 3-2(d), the EDS element mapping image of the Al element of the fluorescent glass ceramic is shown in Figure 3-2(e), the EDS element mapping image of the Gd element of the fluorescent glass ceramic is shown in Figure 3-2(f), the excitation emission 3D spectrum of the fluorescent glass ceramic is shown in Figure 4(a), the excitation spectrum of the fluorescent glass ceramic is shown in Figure 4(b), the emission spectrum of the fluorescent glass ceramic is shown in Figure 4(c), and the Fourier transform infrared spectrum of the fluorescent glass ceramic is shown in Figure 4(d). Figure 5 As shown in Figure 2, the OSL decay curve and OSL integral intensity changes of fluorescent glass ceramics are shown in Figure 2. Figure 6 As shown in Figure 2, the CW-OSL decay curve and exponential fitting curve of the fluorescent glass ceramics are shown in Figure 2. Figure 7 As shown, the TL curve of fluorescent glass ceramics is shown in Figure (8), the CW-OSL dose response curve of fluorescent glass ceramics (0.01-1000Gy) is shown in Figure 9 (a), the CW-OSL attenuation curve of fluorescent glass ceramics (50-1000Gy) is shown in Figure 9 (b), and the OSL cycle characteristic curve of fluorescent glass ceramics is shown in Figure 10 shown.
[0071] Example 4:
[0072] (1) Weigh Na2CO3, CaCO3, NH4H2PO4, B2O3, and Gd2O3 according to the raw material ratio. According to the mass percentage of P2O5 7%, CaO 24%, Na2O 26%, B2O3 42%, ZrO2 1%, and Gd2O3 0.75%, place the weighed raw materials in an agate mortar and grind them for 1 hour to obtain a uniformly mixed powder, which is then transferred to a high-purity corundum crucible;
[0073] (2) placing the powder obtained in step (1) in a muffle furnace at a temperature of 1300° C. and calcining for 1 hour, quickly pouring the melt in the high-purity corundum crucible into deionized water for quenching to obtain a precursor glass, and then transferring it to an oven for drying to obtain a solid glass;
[0074] (3) grinding the solid glass obtained in step (2) in an agate mortar for 4 hours to obtain glass powder;
[0075] (4) Weigh 0.2 g of the powder obtained in step (3) and pour it into a mold with a diameter of 10 mm. Press it into a green disc using a hydraulic press with a holding pressure of 40 MPa for 70 seconds.
[0076] (5) The green disc obtained in step (4) is placed in a muffle furnace for heat treatment. The heat treatment temperature is first kept at 420°C for 3 hours, then kept at 520°C for 3 hours, and finally cooled naturally to room temperature to obtain rare earth Gd 3+ Doped NaCaPO4 fluorescent glass ceramic materials.
[0077] The XRD pattern of the NaCaPO4 glass ceramic obtained in step (5) is shown in Figure 1. Both the crystal peak and the amorphous peak exist, and the peak position and intensity of the crystal peak correspond to the PDF card of NaCaPO4, indicating the existence of the corresponding crystalline phase. Under the excitation of 275nm light source, the emission spectrum measured is shown in Figure 4(b), showing that Gd 3+ The characteristic emission peak position of the doped NaCaPO4 phosphate glass ceramics. The XRD spectrum of the fluorescent glass is shown in Figure 1 (a), the model of the precipitated NaCaPO4 crystal is shown in Figure 1 (b), the excitation spectrum of the fluorescent glass ceramics is shown in Figure 4 (b), the emission spectrum of the fluorescent glass ceramics is shown in Figure 4 (c), and the Fourier transform infrared spectrum of the fluorescent glass ceramics is shown in Figure 4 (d). Figure 5 As shown in Figure 2, the OSL decay curve and OSL integral intensity changes of fluorescent glass ceramics are shown in Figure 2. Figure 6 As shown in Figure 2, the CW-OSL decay curve and exponential fitting curve of the fluorescent glass ceramics are shown in Figure 2. Figure 7 shown.
[0078] Finally, it should be noted that the above embodiments are intended only to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the embodiments, it should be understood by those skilled in the art that modifications or equivalent substitutions to the technical solutions of the present invention do not depart from the spirit and scope of the technical solutions of the present invention and are intended to be encompassed by the claims of the present invention.
Claims
1. A luminescent phosphate fluorescent glass ceramic for gamma-ray radiation dose detection, characterized in that: The luminescent phosphate fluorescent glass ceramic comprises, by mass percentage, 4-7% P2O5, 21-24% CaO, 3-26% Na2O2, 42-45% B2O3, and 1-4% ZrO2. The glass matrix is doped with Gd in the form of a compound. 3+ , wherein the doped gadolinium-containing compound accounts for x of the total mass of other raw materials, 0.1≤x≤0.
75.
2. The luminescent phosphate fluorescent glass ceramic according to claim 1, characterized in that: Doped with Gd 3+ The compound is Gd2O3.
3. The luminescent phosphate fluorescent glass ceramic according to claim 1 or 2, characterized in that: Rare Earth Gd 3+ The dose response of CW-OSL of NaCaPO4-doped fluorescent glass-ceramic material is 0.928 in the range of 0.1-1000Gy after fitting, and R in the range of 50-1000Gy after linear fitting. 2 =0.9992.
4. A method for preparing the luminescent phosphate fluorescent glass ceramic for gamma-ray radiation dose detection according to any one of claims 1 to 3, comprising the following steps: 1) Raw material preparation: weigh the raw materials and mix them evenly to obtain a mixture powder; 2) Melting and quenching: The powder obtained in step 1) is calcined, and after melting, the melt is quenched to obtain a precursor glass, and the precursor glass is ground to obtain a glass powder; 3) Tableting: pouring the glass powder obtained in step 2) into a mold and pressing it into a round green tablet; 4) Heat treatment: The green disc obtained in step 3) is heat treated and cooled to room temperature to obtain rare earth Gd 3+ Doped NaCaPO4 fluorescent glass ceramics.
5. The preparation method according to claim 4, characterized in that: In the step 2), the calcination temperature is 1250-1350° C. and the calcination time is 1-4 hours; The melt was poured into deionized water for quenching.
6. The preparation method according to claim 4, characterized in that: In step 3), a hydraulic press is used for pressing, and the hydraulic press uses a pressure of 20-50 MPa and a holding time of 60-90 seconds.
7. The preparation method according to claim 4, characterized in that: In the step 4), the heat treatment temperature is 400° C.-550° C., and the heat treatment time is 3-6 hours.
8. Use of the luminescent phosphate fluorescent glass ceramic according to any one of claims 1 to 3 in gamma-ray radiation dose detection.